IT Strategy in Maskargo Airlines Industry - Nor Alina, Ismail (2011)
Nowadays, without Information Technology approach, the cargo airline industry or any other industry cannot improve and invest the performance of their own industry. The focus of this paper is discusses more about the IT strategy in the Malaysia Cargo airlines industry (MASKargo) and also to discuss clearly about how IT strategy in the cargo airline industry can help the cargo airlines industry in Malaysia to invest and improve their companies operation management. Furthermore, there are so many purposes that can be found for help the companies and organization of the cargo airlines industry to develop the IT strategy. Hence, Information Technology and airline industry are related to each other and need to use technology strategically because to ensure the operations and also can control and can co-ordinate all the business and other operation management functions.